PERBANDINGAN PENURUNAN TEKANAN DARAH PASIEN BEDAH FRAKTUR DENGAN PREMEDIKASI ANESTESI PETIDIN DAN FENTANIL DI RSUD KOTA BOGOR - Siti Mariam; Kiki Fitriana Dewi; Halimatussa’diyah (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2019)
Premedication of intravenous anesthesia using the drugs petidine and fentanyl causes side effects of hypoventilation or decreased tidal volume and hypotension. This study aims to determine the decrease in blood pressure in fracture surgery patients at RSUD Kota Bogor. This study was conducted on 100 inpatients in the January-December 2018 period who were given the drugs petidine and fentanyl premedication. This type of non-experimental research with the retrospective data collection, research data were analyzed using the Kolmogorov-Sminorv test and the Mann Whitney test. Data taken included: Medical record number, age, sex, duration of surgery and blood pressure 5 minutes before premedication to 1 hour of surgery. The results found more surgical fracture patients occur in men (63%) with an age range of 40-50 years (29%). The duration of the most operations was 1 hour (62%). The most widely used premedication therapy as a narcotic analgesic drug is fentanyl (70%). The most common decrease in blood pressure is petidine (13.93 mmHg) compared to fentanyl (8.34 mm / Hg). Based on statistical results using the Kolmograv-Smirnov test and the Mann-Whitey test p-value (asymp sig. (2-tailed) showed a p-value of 0.05 (0,000) which means that there is a difference in blood pressure reduction between petidine and fentanyl.